“Determinación de niveles de fertilización fosfórica en el rendimiento del frijol cawupi (vigna unguiculata(L) Walp) en el sector de fanaga cunumbuque” - Montilla Huaman, Jimmy Arnold (2014)
This research paper was founded in the "San Luis" property of the ing. Jaime Montilla Sailing, located in the district of Cunumbuque, province of Lamas and region San Martin - Peru. lt was objective; determine a level of phosphate fertilization that will succeed in improving bean yields cowpea (Vigna unguiculata (l) Walp) in field, using the white variety Cumbaza INIA of cowpea, using the same density and planting in all treatments. The statistical design was DBCA with 4 repetitions and 6 treatments, each plot was evaluated, the results were analyzed by analysis of variance and the Duncan's multiple test. In the meteorological data are presented with an average annual rainfall between 1000 to 1400 mm and a mean annual temperature of 25 to 28 ºC. The experimental soil sample a clay textura! class, with an organic matter content of 2.27 %; pH moderately alkaline; in addition, with average content of P205: 337 .53 ppm; K20: 29 ppm. Of the results obtained on the performance of grain adjusted to 14 % of dampness one concludes that there exists a highly significant difference between established treatments, being the T5 (100 kg ha-1 of P205) the fact that 1 bring the major averages of performance and number of pods for plant with 3,289 t. ha-1 and 13, 14 pods for plants respectively overcoming statistically to the averages reached by other treatments. The treatments T5 (100 kg ha-1 of P205) and T4 (80 kg ha-1 of P205) they brought statistically equal averages between if for the weight of 100 grains and 1 number of grains for pod with 17,81 grains and 14,22 g of weight of 100 grains respectively overcoming statistically to the averages obtained by other treatments. Being of great contribution for the agriculture in order to obtain better performance in the bean caupi (Vigna ungu'iculata (L) Walp). KEY WORDS: Performance, phosphorus, caupí, fertilization, soil, fertility.